Implementing technical refinement in high-level athletics: exploring the knowledge schemas of coaches - Kearney, P. E.; Carson, H. J.; Collins, D. (Journal of Sports Sciences, 2018)
This paper explores the approaches adopted by high-level field athletics coaches when attempting to refine an athlete`s already well-established technique (long and triple jump and javelin throwing). Six coaches, who had all coached multiple athletes to multiple major championships, took part in semi-structured interviews focused upon a recent example of technique refinement. Data were analysed using a thematic content analysis. The coaching tools reported were generally consistent with those advised by the existing literature, focusing on attaining "buy-in", utilising part-practice, restoring movement automaticity and securing performance under pressure. Five of the six coaches reported using a systematic sequence of stages to implement the refinement, although the number and content of these stages varied between them. Notably, however, there were no formal sources of knowledge (e.g., coach education or training) provided to inform coaches` decision making. Instead, coaches` decisions were largely based on experience both within and outside the sporting domain. Data offer a useful stimulus for reflection amongst sport practitioners confronted by the problem of technique refinement. Certainly the limited awareness of existing guidelines on technique refinement expressed by the coaches emphasises a need for further collaborative work by researchers and coach educators to disseminate best practice.